РАЗВОЈНИ АСПЕКТИ ТУРИЗМА (Општина Кнић) - Vujović, Slavoljub; Macura, Rajko; Spajić, Jovan (Economics of Agriculture, 2011)
The synthesis of theoretical concepts and empirical research confrms that tourism as an economic activity or economic development model, different from the production activities. The fact that productive activity generated то the development, producing new values, and that tourism creates conditions for the sale of these values in the tourism market, ie. allows for the sale or export of manufactured value in local communitiesspecifcally in the municipality of Knic, confrming tourism development function. This paper explains the development aspects of tourism adequate valorization of tourist attractions in the on place of Knic, later exporting (so-called invisible exports) products and services right here at home. The ontological method-in particular the principle of suffcient reason supports the hypothesis of the possibility of development of the Municipality Knić adequate valorization elements of tourism offer (attractive, communicative and receptive), are particularly interesting. With attractive natural elements are certainly in the frst place. Since the natural-geographical location and other factors related to it, predisposing agriculture and tourism as a main activity and the holders of the overall development of the Serbian economy, Knic could serve as a paradigm for the further development of Serbian economy.